IoT security improvement based on SDN Controller - Abdulrasool A. Abdulsamad; Thair A. Salih (Genius Journals, 2023)
The Internet of Things (IoT) is a promising and modern technology in which devices and things around us are connected to a remotely controlled network. A large number of IoT devices produce large amounts of data, which have a significant impact on the elements of the network and its security. As the various attacks on IoT networks are a source of great concern, mitigating these attacks has become necessary. Because traditional networks do not meet the purpose, it has become essential to search for other techniques to improve the network's ability to deal with these challenges. Hence the role of Software Defined Networking (SDN), a technology that has recently emerged to support the growth of large organizations and offer benefits that may be challenging to obtain in conventional networks, allows for the expansion and updating of network resources by appropriate needs, makes it easier to keep up with the ongoing development of the network structure, and lowers numerous expenses and costs In this study, we discuss the concepts of the IoTs, then explain SDN technology, explain the mechanism of SDN networks, and discuss security problems and ways to solve them using SDN technology. We present a practical scheme that we have implemented in reality using OpenVswitch with Raspberry Pi and RYU SDN Controller In addition to NodeMCU. The IoT Network is designed and then implemented in reality. A DDOS attack execution test is applied to these devices, and the attack is prevented and stopped using SDN technology. The Raspberry Pi 4B is used with the USB to Ethernet Adapter in addition to the OVS as a switch that supports the OpenFlow protocol, and the NodeMCU with ESP is used as an IoT device
Keywords: Internet of Things; Software-Defined-Network; Security; Distributed Denial of Service